2006
DOI: 10.1111/j.1439-0418.2005.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐plant acceptance and performance of Tetranychus urticae (Acari, Tetranychidae)

Abstract: Tetranychus urticae is a serious pest of several crops worldwide. It performs differentially on diverse hostplant species. Because dispersion is mainly passive, the process of host-plant selection should be viewed in terms of host-plant acceptance and not in terms of host finding. The objectives of this study were to investigate: (1) the acceptance of strawberry (S) in comparison with onion (O), leek (L) and parsley (P) by T. urticae; and (2) the suitability of these host plants for the performance of T. urtic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
1
27
0
3
Order By: Relevance
“…A redução nos valores de r m de Tetranychus spp. sobre plantas menos favoráveis ao seu desenvolvimento pode ocorrer porque o ácaro necessita alocar energia, por exemplo, para destoxificação causada por compostos secundários produzidos pela planta hospedeira ou para evitar plantas com esses compostos secundários que são tóxicos (HELLE & SABELIS, 1985;GRECO et al, 2006). No entanto, KRIPS et al (1998) observaram que, em cultivares de gérbera resistentes ao T. urticae, mesmo após 10 gerações desse ácaro, o valor de r m se manteve baixo quando comparado à cultivar suscetível.…”
Section: -----------------------------------------------------------Punclassified
See 1 more Smart Citation
“…A redução nos valores de r m de Tetranychus spp. sobre plantas menos favoráveis ao seu desenvolvimento pode ocorrer porque o ácaro necessita alocar energia, por exemplo, para destoxificação causada por compostos secundários produzidos pela planta hospedeira ou para evitar plantas com esses compostos secundários que são tóxicos (HELLE & SABELIS, 1985;GRECO et al, 2006). No entanto, KRIPS et al (1998) observaram que, em cultivares de gérbera resistentes ao T. urticae, mesmo após 10 gerações desse ácaro, o valor de r m se manteve baixo quando comparado à cultivar suscetível.…”
Section: -----------------------------------------------------------Punclassified
“…O desenvolvimento de T. urticae pode ser influenciado pela espécie de planta utilizada como hospedeira, assim como pode ocorrer variação intraespecífica, em função dos diferentes genótipos utilizados nos cultivos comerciais (KRIPS et al, 1998;GRECO et al, 2006; VAN DEN BOOM et al, 2003). No Brasil, há estudos que comparam o desenvolvimento de T. urticae em diferentes espécies e cultivares de plantas de importância econômica, como em algodoeiro Gossypium hirsutum (SILVA et al, 1985a;ESTEVES FILHO et al, 2010), morangueiro Fragaria x ananassa (LOURENÇÃO et al, 2000), tomateiro Lycopersicon spp.…”
Section: Introductionunclassified
“…Spider mites may escape from unsuitable plants when they are inoculated on them. Greco et al (2006) reported the repeated escape of T. urticae from onion and leek as unsuitable plants, compared to strawberry as a suitable plant. With the combination of borage and borage in our experiments, we found that mites frequently moved between the two leaf discs during the 24 h observation.…”
Section: Discussionmentioning
confidence: 99%
“…To test settlement of females on borage and strawberry for 16 spider mite species, excluding T. evansi and T. ezoensis which failed to lay eggs on either strawberry or borage, we measured movement of adult females from a test plant where they had been released ('origin'), to another plant ('fate') (Yano et al, 1998;Greco et al, 2006). Two square leaf discs (10ϫ10 mm) were connected with a bridge of parafilm (1.5 mm width and 50 mm length), then five 2-3-d-old adult females were inoculated onto the 'origin' leaf disc and their positions-i.e., either 'origin' or 'fate'-were recorded after 24 h according to the methods of Yano et al (1998).…”
Section: Host Plant Acceptance: Movement Of Femalesmentioning
confidence: 99%
See 1 more Smart Citation